Pengaruh Profitabilitas, Leverage, Likuiditas dan Aktivitas terhadap Nilai Perusahaan pada Sub Sektor Food & Staples Retailing - Binastuti, Sugiharti; Syaberina Shalwa Annishya; Upi Niarti; Paddery (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The establishment of a company aims to generate profits and improve the welfare of its owners. However, to generate profits, good strategy and management are required because they will affect the value of the company. The data used in this study is secondary data in the form of financial statements and annual reports of companies in the food & staples retailing sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023, with a sample size of 45. The testing stages conducted include classical assumption tests (normality test, multicollinearity test, heteroskedasticity test, autocorrelation test), multiple linear regression, F-test, T-test, and coefficient of determination. The sampling method used in this study is non-probability sampling with purposive sampling technique. The results of the study indicate that the variables of profitability, leverage, liquidity, and activity simultaneously influence company value. Profitability and leverage influence company value, while liquidity and activity do not influence company value. Keywords: activity, company value, leverage, liquidity, profitability